Second-Line Anti-Tuberculosis Drugs Susceptibility Pattern in Multidrug-resistant Tuberculosis Patients at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Suwandi, Shianny Natasha; Kulsum, Iceu Dimas; Andriyoko, Basti (Althea Medical Journal, 2024)
Background: Indonesia has the second-highest tuberculosis prevalence in the world. Moreover, Indonesia is among the 30 countries with the highest burden of multidrug-resistant tuberculosis (MDR-TB). This study aimed to determine the pattern of second-line anti-tuberculosis drug resistance in MDR-TB patients.Method: This study was a descriptive cross-sectional using data from MDR-TB patients aged 18 years and older, diagnosed with drug-resistant TB at Dr. Hasan Sadikin General Hospital from December 2021 to June 2022. Total sampling was used. Data on age, gender, history of previous antituberculosis drug treatment and second-line antituberculosis drug susceptibility test results were collected. Resistance distribution patterns were identified using the Line Probe Assay (LPA) and the Mycobacteria Growth Indicator Tube (MGIT) test.Results: Of 134 data retrieved, only 82 data were complete. The median age of the patients was 42 years (range 27-51 years), predominantly female (53.7%), without a history of antituberculosis drug treatment (52.4%). The highest number of resistances was resistant to high dose isoniazid (43.9%), followed by low dose fluoroquinolone (14.6%). Among patients who were resistant to low dose moxifloxacin, 16.67% of patients were still sensitive to high dose moxifloxacin. There was no resistance to bedaquiline.Conclusions: Almost half of the patients are resistant to high dose isoniazid, followed by resistance to low dose fluoroquinolone. These finding are expected to be taken into consideration by clinicians in making decisions on the diagnosis or management of MDR-TB patients and can further serve as input for the government in implementing MDR-TB control programs in Indonesia.